Highly simplified blue phosphorescent organic light-emitting diodes incorporating exciplex-forming co-host assisting energy transfer - Xu, Ting (2020)
The exciplex-forming mixed host with doped phosphorescent dye shows potential to realize high performance phosphorescent organic light emitting didoes (PhOLEDs). Herein, we report a novel exciplex-forming co-host architecture by combining N,N,10-triphenyl-10H-spiro[acridine-9,9'-fluoren]-3'-amine (SAFDPA) with 4,7-diphenyl-1,10-phenanthroline (Bphen) and its further application in a highly simplified blue phosphorescent OLED structure doped with Iridium(III)bis[(4,6-difluorophenyl)-pyridinato-N, C2′] picolinate (FIrpic). The designed blue emitting OLEDs using SAFDPA: Bphen (1:1, w- w) mixed host architecture show simpler device structure, lower working voltage, better efficiency and better stability than those of the reference device. Particularly, Power efficiency of devices with exciplex-forming co-host is significantly enhanced compared with reference device. An effective and synergistic strategy to design highly simplified PhOLEDs helps to simplify fabrication process and popularize OLEDs technology.